Native language processing is influenced by L2-to-L1 translation ambiguity. Issue 3 (2nd April 2020) - Jouravlev, Olessia; Jared, Debra
ABSTRACT: Words of one language often have multiple translations into another language. Does mapping of an L2 word onto multiple L1 words impact how these L1 words are represented in the bilingual lexicon? Russian-English bilinguals decided on the lexical status (Exp1) or the conceptual relatedness (Exp2) of pairs of Russian words that had the same or different translations in English. We obtained evidence for a facilitative effect of L2-to-L1 translation ambiguity. In Exp1, bilinguals were faster to respond to a Russian target if a prime had the same vs. different English translation as the target. Further, the magnitude of the N400 ERP component was reduced and the P200 was enhanced in the translation ambiguous compared to non-ambiguous condition. In Exp2, translation alternatives were rated as being more conceptually similar than words with different translations. Thus, the presence of a shared L2 translation leads to some convergence of corresponding L1 lexico-conceptual representations.